Analysing the Role of Conti Entertain as a Gateway to Digital Gambling Among Teenagers Sharia Perspective: Challenges and Solutions - Mariam Elbanna; Muthoifin; Andri Nirwana; Mahmudulhassan (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to analyze the role of Conti Entertain, a digital entertainment platform, as a gateway to gambling behavior among adolescents, focusing on the challenges and potential solutions. With the rapid growth of digital technology, platforms like Conti Entertain, which integrate gaming and entertainment with monetary incentives, have increasingly attracted young audiences. Theoretical framework: Theoretical underpinnings of this research draw from theories of adolescent cognitive development, social influence, and digital consumer protection. Literature Review: A literature review highlights that digital gambling, particularly through mechanisms like loot boxes and random rewards, has become a growing concern within the digital entertainment ecosystem. Methods: This research adopts a qualitative methodology using a case study approach. Data collection methods include in-depth interviews with adolescents, parents, and experts in digital media, psychology, and law, along with content analysis of features within Conti Entertain that promote gambling tendencies. Results: The findings reveal that Conti Entertain significantly influences gambling-like behaviors through mechanisms such as loot boxes, random rewards, and monetization features that blur the line between gaming and gambling. Adolescents are particularly susceptible to these tactics due to their developing cognitive control and peer influence. The study identifies inadequate regulations and lack of parental supervision as major challenges aggravating the issue. Implications: The implications of this study underscore the necessity for stricter regulations on digital entertainment platforms to protect young users from exploitative monetization schemes. Parental awareness and active engagement in monitoring online activities are equally critical. Novelty: The novelty of this research lies in its focus on Conti Entertain as a specific case study within the broader digital gambling landscape. These findings contribute significantly to understanding the link between digital entertainment and gambling behavior among adolescents, offering practical solutions to address this pressing issue.